Decoding costume and make-up elements in reading communism via independent documentary / Mohd. Nor Shahizan Ali...[et al.] - Shahizan Ali, Mohd Nor; Ameera, Neesa; Mohd Khalis, Faryna (2019)
Regarding the issue of independent documentary, the key question to be considered is whether the message conveyed to target groups or intended audiences is fully achieved. The usage of costume and make-up to convey the message of an independent documentary is seen as an added value for audiences to digest the producers’ idea. Using an independent documentary ‘The Last Communist (2006)’(TLC) work of Amir Muhammad, this study discusses the ‘reading’ of costume and make-up based on the cultural, ideology and technological narrative message. These costume and make-up represent the producers’ idea and constructs a connotation meaning for audiences to consume as they want. The costume and make-up are highly posed and are set in descriptive meaning to make them relevant across the globe. They represent actual places or tragedy, and they document witness, which symbolically represents moods such as ‘contentment’ and ‘freedom’. This study implied a focus group discussion with eight informants (final year undergraduate students comprising three boys and five girls studying at Universiti Kebangsaan Malaysia) whom have watched ‘The Last Communist (2006)’. The topic of discussion is focused only on the costume and make-up. It is debatable that costume and make-up reading cannot be described adequately in formal terms only. Rather, they are considered to be visual representations of metaphorical thoughts or concepts and the changing of time and mass. The implication will then be the ability to add more natural presentation and make the independent documentary more appealing. This study suggests the selection of costume and make-up by a producer that represents cultural and technological elements and how they have affected the reading of the post-independence group, thereby making this independent documentary as a byproduct quietly injecting the historiography and the struggle of the communists.